The Anti-Colon Cancer Effects of Essential Oil of Curcuma phaeocaulis Through Tumour Vessel Normalisation - Feng, Yewen; Deng, Lu; Guo, Hengrui; Zhao, Yumin; Peng, Fu; Wang, Gang; Yu, Chenghao (Frontiers in Oncology, 2021)
Background: Normalising tumour vessels had become a significant research focus in tumour treatment research in recent years. Curcumae rhizoma (CR) is an essential plant in traditional Chinese medicine as it promotes blood circulation and removes blood stasis. Similarly, CR improves local blood circulation. Purpose: We explored the anti-colon cancer effects of essential oil from CR (OCR) by investigating its role in normalising tumour vessels. We also provided a basis for research and development into new anti-cancer drugs. Methods: We used colon cancer as a research focus to investigate OCR. We established an in vitro co-culture model of colon cancer cells and human umbilical vein endothelial cells (HUVEC). We also established an in vivo subcutaneous implant colon cancer model in nude mice. These studies allowed us to evaluate the comprehensive effects of OCR in in vivo and in vitro colon cancer and its role in normalising tumour blood vessels. Results: In vitro, we found that OCR inhibited Human colon cancer cells (HCT116) and HUVEC cell proliferation and inhibited vascular endothelial growth factor-a (VEGFa) mRNA and protein expression in HUVECs in a co-culture system. Our in vivo studies showed that OCR inhibited colon cancer tumour growth, reduced angiogenesis in tumours and increased vascular endothelial (VE)-cadherin and pericyte coverage in tumour vessels. Conclusions: OCR inhibited colon cancer growth both in in vivo and in vitro models, reduced angiogenesis in tumours, improved tumour vessel structures and normalised tumour vessels.